Effect of eight weeks endurance exercise on liver enzymes in stopping drug women with methadone - Asad, Mohammad Reza; Haddadi, Farah; Rostami Nejad, Mazhar; Sokhtehzari, Saied (Archives of Advances in Biosciences, 2013)
Previous studies indicated that endurance exercise decreases levels of liver enzymes. The aim of this study was to determine the effect of endurance exercise on liver enzymes in eight weeks in Iranian women who are stopping the drug with methadone. sixty Iranian women prisoners including 30 cases as experimental group and 30 volunteers served as control. The mean age, height, weight, percent of BF, BMI and vo2max of experimental group was 33/8 years, 162/2 cm, 62/2 kg, 33/10, 24/22 and 16/18 ml/kg respectively. Experimental group was should run with 65%vo2max for 2 weeks (3 sessions in a week and for 25 minutes), with 65-75% vo2max for 3 weeks (3 sessions in a week for 35 minutes) and with 75-85% vo2max for 3 weeks (3 sessions in a week for 40 minutes). The blood samples were collected in amount of 5 ml 48 hours before the first session and after the last session of the protocol. Other causes of abnormal liver enzymes such as hepatitis and autoimmune disorders etc. were excluded. The level of ALT (alanine aminotransferase) between experimental group and control group in post-test was not significant. But it was significantly differenced for level of AST (aspartate aminotransferase) when we compared the groups. On the other hands, the level of ALT and AST in post-test in contrast with pre-test in experimental group was not significant. The result of this study showed that endurance exercise for eight weeks did not normalize the level of ALT and AST of the study group. Therefore more investigation such as diet habits, demographic and other risk factors is recommended for these types of patients.